Interações entre professores e alunos em grupos acadêmicos na rede social Facebook: um estudo à luz do paradigma da complexidade - Murta, Cláudia Almeida Rodrigues (2016)
The sociocultural transformations promoted by digital technologies have enabled the development of social networks on the Internet. Networks such as Facebook have become contemporary interaction spaces that are being appropriated by different social groups, including academic ones. Understanding the complexity of the interactions displayed by language practices, the different appropriations that groups of professors and university students give to the social network site, as well as the benefits that they may have from the interactions was what I aimed at in this research. To that end, I have based my research on knowledge about the language in use (LARSEN-FREEMAN; CAMERON, 2008), on computer mediated interactions (PRIMO, 2003), on social networking sites, as well as on social capital (RECUERO, 2009, 2012, 2014) generated in the interactions in this digital media. I have looked for empirical evidence of the properties of complex adaptive systems, according to the Five Graces Group (2009), in the interactions of five groups on Facebook, of professors and students of the area of Languages and Literature of three universities. In addition, I have analyzed the appropriations that the participants of the groups made of the social network site from the bonds they established in their relations and the benefits they had while interacting in these groups, following the social capital categories of Bertolini and Bravo (2004). I understand through the analysis of the data that the group interactions of professors and students on Facebook materialize in hybrid language practices which are influenced by the mediating contexts, the academy and the social networking site. However, the performance of the network site as a control parameter was stronger, leading participants to prefer the language practices typical of such context. In the complex adaptive system of interactions, the control is distributed, so the emergence of behaviors is not determined by a leader (top down); it emerges from local interactions that aim at solving immediate problems. The practices of language in the social network site are established in nuances of mutual interaction that are indicative of the social ties developed in the groups.Social bonds are multiplexed, which means, they are strong, weak, of maintenance and associative, and change over time according to the established interactions and appropriations made by the participants in the groups. The appropriations demand investments from the participants and produce benefits, thus generating social capital that can be enjoyed individually and by the group. I believe that understanding the complexity of interactions on social networking sites can help us understand the situated nature of language use, its continuing flow of change in different contexts, including the academic. Also, it sheds light to the different uses that sociocultural groups give to digital interactive platforms.